An integrating text retrieval framework for Digital Ecosystems Paradigm - Zhu, Dengya; Dreher, Heinz (IEEE, 2007)
The purpose of the research is to provide effective information retrieval services for digital ?organisms? in a digital ecosystem by leveraging the power of Web searching technology. A novel integrating digital ecosystem search framework (a new digital organism) is proposed which employs the Web search technology and traditional database searching techniques to provide economic organisms with comprehensive, dynamic, and organization-oriented information retrieval ranging from the Internet to personal (semantic) desktop.